Yellowing-resistant halogen-free environment-friendly flame-retardant PP composite material and preparation method thereof

By using pyropipe-based expanded flame retardant, tin-based flame retardant smoke inhibitor, inorganic filler and glass powder in the polypropylene composite material, a dense carbon layer is formed and its strength is enhanced, and the problem of difficult to take into account both flame retardant and mechanical properties in the prior art is solved, and a halogen-free environmentally friendly polypropylene composite material with high flame retardant and yellowing resistance is achieved.

CN119842152APending Publication Date: 2025-04-18YUNNAN TIN IND TIN MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510116946.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to develop halogen-free environmentally friendly flame-retardant polypropylene composite materials that can achieve UL94-5VA grade flame retardant and yellowing resistance without reducing the mechanical properties of the material. Especially when too much flame retardant is added, the flame retardant and mechanical properties of the material will be affected.

Method used

By introducing components such as pyropipe-based expansion flame retardant, tin-based flame retardant smoke inhibitor, inorganic filler and glass powder, the synergistic flame retardant effect in the system is promoted, a dense carbon layer is formed and its strength is enhanced, and the use of glass fibers is avoided to simplify the preparation process.

Benefits of technology

It realizes the high flame retardant properties and yellowing resistance of polypropylene composite materials, can maintain flame retardant effect under strict conditions, and passes UL94-5VA grade test, and the preparation process is simple and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842152A_ABST
    Figure CN119842152A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-yellowing halogen-free environment-friendly flame-retardant PP composite material and a preparation method thereof. The composite material is prepared from the following components in percentage by mass: 55 to 70 percent of polypropylene master batch, 20 to 35 percent of pyropethyl intumescent flame retardant, 1 to 3 percent of hypophosphite flame retardant, 2 to 5 percent of inorganic filler, 0.5 to 3 percent of tin-based flame-retardant smoke suppressant, 2 to 7 percent of glass powder, 1 to 4 percent of compatilizer, 0.3 to 0.5 percent of antioxidant and 0.2 to 0.4 percent of anti-dripping agent. The flame-retardant polypropylene composite material disclosed by the invention not only has excellent flame-retardant performance, but also has the characteristic of yellowing resistance, the preparation process is simple, convenient and efficient, and a high-performance and reliable polypropylene composite material solution is provided for the electronic and electric appliance industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of flame-retardant polypropylene composite materials, and specifically relates to a UL94-5VA grade yellowing-resistant halogen-free environmentally friendly flame-retardant PP composite material for electronic appliances and a preparation method thereof. Background Art

[0002] As a synthetic resin, polypropylene (PP) stands out for its unique lightweight properties, with a density of only 0.9 to 0.91 g / cm3. This means that with the same raw material weight, PP can produce more products with a comparable volume. PP is not only non-toxic and odorless, but also surpasses low-pressure polyethylene in strength, stiffness and heat resistance. It also has excellent mechanical properties, chemical corrosion resistance and good molding and processing properties, which have made it widely used in home appliances and electronic appliances. Although polypropylene has many advantages, one of its significant disadvantages is its flammability and severe melting droplets during combustion. In view of this, flame retardant modification of PP has become an inevitable choice. Especially in recent years, with the increasingly stringent flame retardant regulations and the improvement of flame retardant requirements, PP materials used for internal and external parts of home appliances such as refrigerators, air conditioners, and washing machines must meet the UL94-5VA grade. This grade requires that the material not only meets the standard in the strip test, but also does not burn through after multiple contacts with the flame. In addition, PP materials for electronic appliances must not only meet the 5VA flame retardant performance, but also pass the double 85 test (that is, after being placed at 85°C and 85% relative humidity for 96 hours, the color difference value ΔE*ab is less than 2) to ensure its yellowing resistance.

[0003] At present, it is difficult for a single flame retardant to meet the above stringent requirements, and the promotion of environmental protection policies has made halogen-free a development trend. Therefore, it is inevitable to develop halogen-free and environmentally friendly intumescent composite flame retardants. In PP, the commonly used halogen-free flame retardants are phosphorus-nitrogen intumescent flame retardants, such as ammonium polyphosphate (APP) system and piperazine pyrophosphate (PAPP) system. However, for 5VA grade polypropylene, especially thinner materials, a higher amount of flame retardant addition is required. But when too much flame retardant is added, it may not only fail to pass the 5VA test, but also cause a significant decrease in the mechanical properties of the material. To solve this problem, glass fiber (GF) is usually added to reinforce the material. However, adding GF to the APP and PAPP systems may cause APP to decompose and reduce the flame retardant efficiency. Therefore, the PAPP system is considered to be more suitable for PP flame retardancy. Chinese patent CN106995559A proposes a method for preparing UL94-5VA grade high GWIT reinforced polypropylene by adding piperazine pyrophosphate-based halogen-free flame retardant masterbatch and using glass fiber for connecting support. However, this method has some problems, such as the wick effect of glass fiber will weaken the strength of the carbon layer of the expanded flame retardant, making it easy to collapse, thereby reducing the flame retardant performance. In addition, it will also lead to reduced PP fluidity, floating fiber phenomenon, difficulty in molding, brittle materials and other problems. Similar problems also appear in other patents, such as CN200810120362, CN201010613173, CN201110233266 and CN201210070457. Therefore, it is of great significance to develop a polypropylene composite material that has both high flame retardant properties and passes the double 85 yellowing resistance test. Summary of the invention

[0004] The present invention aims to solve the problems existing in the prior art and provide a high-performance halogen-free flame-retardant polypropylene composite material for electronic appliances and a preparation method thereof. The halogen-free flame-retardant polypropylene composite material can not only achieve the flame retardant grade of UL94-5VA, but also has excellent yellowing resistance.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] A yellowing-resistant, halogen-free, environmentally friendly, flame-retardant PP composite material, the composite material being composed of the following components in percentage by mass: 55-70% of polypropylene masterbatch, 20-35% of pyropyroxene-based intumescent flame retardant, 1-3% of hypophosphite flame retardant, 2-5% of inorganic filler, 0.5-3% of tin-based flame retardant and smoke suppressant, 2-5% of glass powder, 1-4% of compatibilizer, 0.3-0.5% of antioxidant and 0.2-0.4% of anti-dripping agent.

[0007] Furthermore, the polypropylene masterbatch is homopolymer polypropylene, and the melt index is ≥20g / 10min at 230°C and 2.16kg.

[0008] Furthermore, the piperazine pyrophosphate intumescent flame retardant is compounded by piperazine pyrophosphate and melamine polyphosphate in a mass ratio of 3:2 to 7:3.

[0009] Furthermore, the hypophosphite flame retardant is one of aluminum hypophosphite and diethyl aluminum hypophosphite.

[0010] Furthermore, the inorganic filler is one of wollastonite and kaolin with a whiteness of 90 or more.

[0011] Furthermore, the tin-based flame retardant and smoke suppressant is one of nano-grade zinc stannate and hydroxy zinc stannate.

[0012] Furthermore, the glass powder is FJ373 type glass powder with a melting point of 450° C. and a whiteness of 88 or above.

[0013] Furthermore, the compatibilizer is maleic anhydride grafted polypropylene, and its maleic anhydride grafting rate is ≥1%.

[0014] Furthermore, the antioxidant is prepared by compounding pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris[2,4-di-tert-butylphenyl]phosphite in a mass ratio of 1:2.

[0015] Furthermore, the anti-dripping agent is polytetrafluoroethylene powder.

[0016] The preparation method of the yellowing-resistant halogen-free environmentally friendly flame-retardant PP composite material of the present invention is to first dry the pyropyrene-based flame retardant, hypophosphite flame retardant, tin-based flame retardant and smoke suppressant, inorganic filler and glass powder, and then mix them with polypropylene masterbatch, compatibilizer, antioxidant and anti-dripping agent, and then melt-extrude the mixture to obtain the UL94-5VA grade yellowing-resistant halogen-free environmentally friendly flame-retardant PP composite material.

[0017] Furthermore, the drying of the pyropyrite flame retardant, hypophosphite flame retardant, tin-based flame retardant and smoke suppressant, inorganic filler and glass powder is performed at 70-90° C. for 12 hours; and the melt-extrusion of the mixture is performed by feeding the mixture into a 20-type twin-screw extruder for melt-extrusion.

[0018] Compared with the existing preparation methods, the present invention has the following significant advantages:

[0019] The present invention promotes the synergistic flame retardant effect in the system by introducing components such as pyrophosphate-based intumescent flame retardant, synergist (tin-based flame retardant and smoke suppressant), inorganic filler and glass powder. These components can not only catalyze and promote the formation of a large number of dense carbon layers on the surface of the material, but also significantly enhance the strength of the carbon layer, making it difficult to collapse, and effectively improve the flame retardant properties of the polypropylene composite material. Among the composite material components of the present invention, the polypropylene masterbatch is an essential material for preparing a flame-retardant PP composite material. The flame retardant system composed of the pyrophosphate-based intumescent flame retardant and the hypophosphite flame retardant has flame retardant effect, heat stability and water precipitation resistance. In particular, the pyrophosphate-based intumescent flame retardant is compounded by pyrophosphate piperazine and melamine polyphosphate in a mass ratio of 3:2 to 7:3, which can play a better synergistic flame retardant effect. The hypophosphite flame retardant uses one of aluminum hypophosphite and diethyl aluminum hypophosphite, which can give full play to the carbonization effect of aluminum hypophosphite and diethyl aluminum hypophosphite. Tin-based flame retardants and smoke suppressants play a synergistic and smoke suppressing role. In particular, tin-based flame retardants and smoke suppressants use one of nano-grade zinc stannate and hydroxy zinc stannate, which can make full use of the flame retardant and smoke suppressant properties of these materials to improve flame retardant efficiency and reduce smoke release. Inorganic fillers use wollastonite and kaolin with a whiteness of more than 90 to ensure that better transparency and surface gloss can be provided in plastic products. In particular, the coexistence of glass powder and organic fillers can be compounded with other systems to produce a synergistic effect, showing a ceramic effect during the combustion process, so that the carbon layer can form a dense ceramic skeleton structure, thereby ensuring that the plate-shaped sample is not penetrated during combustion, and ultimately significantly improving the flame retardant level of the sample. The use of FJ373 glass powder with a melting point of 450°C and a whiteness of more than 88 can ensure the ceramic effect of the carbon layer structure. The role of the compatibilizer is to improve or promote the compatibility between different materials. Maleic anhydride grafted polypropylene can introduce polar groups to improve weather resistance, improve filling performance, and enhance the adhesion between polar and non-polar materials. The function of antioxidant is to prevent or delay the oxidation of other substances. The antioxidant is compounded with tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester and tris[2.4-di-tert-butylphenyl] phosphite in a mass ratio of 1:2, which can improve the antioxidant properties of plastic products and ensure the quality and stability of the products. The function of anti-drip agent is to prevent or reduce the dripping phenomenon of plastic materials during high-temperature treatment. Using polytetrafluoroethylene powder as a drip agent has a good anti-drip effect.

[0020] The polypropylene composite material prepared by the present invention can have a limiting oxygen index of more than 45%. Under normal conditions (temperature 23±2°C, humidity 50±5%, for 48 hours), 2.0mm strip specimens and plate specimens successfully passed the UL94-5VA grade test. Even under more stringent conditions, that is, after aging for 168 hours at 70±2°C, the flame retardant performance remains unchanged, and the strip and plate specimens can still pass the UL94-5VA grade test smoothly. The flame retardant system adopted by the present invention is a non-APP system. After being placed continuously for 96 hours under an environment of 85°C and 85% relative humidity (RH), the color difference value ΔE*ab is less than 2, while the flame retardant effect is maintained, and the UL94-5VA test with a thickness of 2.0mm can still be successfully passed. It is particularly worth mentioning that the present invention does not introduce glass fiber in the preparation process, avoids the complexity of processing and molding, and ensures the smoothness and efficiency of the production process. This feature enables the composite material to fully meet the performance requirements of polypropylene materials for electronic appliances, and ensures the appearance quality and long-term stability of the product. The preparation method of the invention is simple and easy to implement, and the composite flame retardant has good compatibility with the resin matrix. In the process of water-cooling and drawing, no undesirable phenomena such as material breaking or precipitation occur, thereby ensuring the smoothness of the production process and the stability of product quality.

[0021] In summary, the present invention not only has excellent flame retardant properties, but also has the characteristics of yellowing resistance, and the preparation process is simple and efficient, providing a high-performance and reliable polypropylene composite material solution for the electronic and electrical industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a photograph of a 5VA plate-shaped test sample of a halogen-free flame-retardant polypropylene composite material having a flame retardant rating of UL94-5VA and yellowing resistance prepared in Example 1, which has not been burned through;

[0023] Figure 2 This is a photo of the carbon residue of the halogen-free flame-retardant polypropylene composite material that has passed the UL94-5VA flame retardancy rating and is resistant to yellowing in Example 2;

[0024] Figure 3 The photographs of the double 85 test process of the halogen-free flame retardant polypropylene composite material of Example 3 which passed the UL94-5VA flame retardant rating and was resistant to yellowing are shown. DETAILED DESCRIPTION

[0025] The present invention is described in detail below in combination with the embodiments, test data and drawings. The embodiments described are only partial embodiments of the present invention, but the protection scope of the present invention is not limited to the embodiments.

[0026] The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material of the present invention is composed of the following components in mass fraction: 55-70% of polypropylene masterbatch, 20-35% of pyropyroxene-based intumescent flame retardant, 1-3% of hypophosphite flame retardant, 2-5% of inorganic filler, 0.5-3% of tin-based flame retardant and smoke suppressant, 2-5% of glass powder, 1-4% of compatibilizer, 0.3-0.5% of antioxidant and 0.2-0.4% of anti-dripping agent.

[0027] The preferred polypropylene masterbatch of the present invention is homopolymer polypropylene, and the melt index is ≥20g / 10min at 230°C and 2.16kg. The preferred pyrophosphate-based intumescent flame retardant is compounded by piperazine pyrophosphate and melamine polyphosphate in a mass ratio of 3:2 to 7:3. The preferred hypophosphite flame retardant is one of aluminum hypophosphite and diethyl aluminum hypophosphite. The preferred inorganic filler is one of wollastonite and kaolin with a whiteness of more than 90. The preferred tin-based flame retardant and smoke suppressant is one of nano-grade zinc stannate and hydroxy zinc stannate. The preferred glass powder is FJ373 type glass powder with a melting point of 450°C and a whiteness of more than 88. The preferred compatibilizer is maleic anhydride grafted polypropylene (PP-g-MAH), and its maleic anhydride grafting rate is ≥1%. The preferred antioxidant is a compound of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester (i.e. antioxidant 1010) and tris[2,4-di-tert-butylphenyl] phosphite (i.e. antioxidant 168) in a mass ratio of 1:2. The preferred anti-dripping agent is polytetrafluoroethylene powder.

[0028] The preparation method of the yellowing-resistant halogen-free environmentally friendly flame-retardant PP composite material of the present invention is as follows: first, the pyropyrene-based flame retardant, hypophosphite flame retardant, tin-based flame retardant and smoke suppressant, inorganic filler and glass powder are dried at 70-90°C for 12 hours, and then put into a high-speed mixer with polypropylene masterbatch, compatibilizer, antioxidant and anti-dripping agent for high-speed stirring for 6-8 minutes to ensure that each component is evenly dispersed; finally, the mixture is fed into a 20-type twin-screw extruder for melt extrusion to obtain a UL94-5VA-grade yellowing-resistant halogen-free environmentally friendly flame-retardant PP composite material. The process parameters of the 20-type twin-screw extruder during extrusion are set as follows: temperature 175-190°C, main engine speed 300-400rpm, feeding speed 15-20Hz, vacuum degree -0.08MPa.

[0029] Example 1

[0030] Weigh 1050g of piperazine pyrophosphate, 450g of melamine polyphosphate, 100g of aluminum hypophosphite, 225g of wollastonite with a whiteness of 92, 200g of FJ373 glass powder, and 25g of nano-grade zinc stannate, and dry them at 90°C for 12h, then weigh 2815g of homopolypropylene with a melt index of 25g / 10min at 230°C and 2.16kg, 100g of PP-g-MAH compatibilizer, 5g of antioxidant 1010, 10g of antioxidant 168, and 20g of polytetrafluoroethylene powder. Mix the above materials and put them into a high-speed mixer for high-speed stirring for 8min. Subsequently, the mixture is fed from the main feeding port into a 20-type twin-screw extruder for melt extrusion (twin-screw extruder parameters are: temperature 180°C, rotation speed 350rpm, feeding speed 18Hz, vacuum degree -0.08MPa) to obtain halogen-free, environmentally friendly, flame-retardant polypropylene composite material particles, and the particles are dried at 80°C for 3h.

[0031] Standard specimens were injected into the injection molding machine for flame retardant and double 85 performance tests, and the injection temperature was set at 180~195℃.

[0032] Example 2

[0033] Weigh 980g of piperazine pyrophosphate, 420g of melamine polyphosphate, 100g of diethyl aluminum hypophosphite, 200g of kaolin, 334g of glass powder with a whiteness of 90, and 25g of nano zinc stannate, dry at 80°C for 12h, then weigh 2806g of homopolypropylene with a melt index of 20g / 10min at 230°C and 2.16kg, 100g of PP-g-MAH compatibilizer, 5g of antioxidant 1010, 10g of antioxidant 168, and 20g of polytetrafluoroethylene powder. Mix the above materials and put them into a high-speed mixer for high-speed stirring for 6min. Subsequently, the mixture was fed from the main feeding port into a 20-type twin-screw extruder for melt extrusion (twin-screw extruder parameters were: temperature 190°C, rotation speed 400rpm, feeding speed 20Hz, vacuum degree -0.08MPa) to obtain halogen-free, environmentally friendly, flame-retardant polypropylene composite material particles, which were then dried at 80°C for 3h.

[0034] Standard specimens were injected into the injection molding machine for flame retardant and double 85 performance tests, and the injection temperature was set at 180~195℃.

[0035] Example 3

[0036] Weigh 900g of piperazine pyrophosphate, 600g of melamine polyphosphate, 50g of aluminum hypophosphite, 250g of wollastonite, 200g of glass powder, and 25g of nano-grade zinc hydroxystannate, and dry them at 70°C for 12h. Then weigh 2840g of homopolymer polypropylene with a melt index of 23g / 10min at 230°C and 2.16kg, 100g of PP-g-MAH compatibilizer, 5g of antioxidant 1010, 10g of antioxidant 168, and 20g of polytetrafluoroethylene powder. Mix the above materials and put them into a high-speed mixer for high-speed stirring for 7min. Then feed the mixture from the main feeding port into a 20-type twin-screw extruder for melt extrusion (twin-screw extruder parameters are: temperature 175°C, speed 300rpm, feeding speed 15Hz, vacuum degree -0.08MPa), and obtain halogen-free environmentally friendly flame-retardant polypropylene composite particles, and then dry the particles at 80°C for 3h.

[0037] Standard specimens were injected into the injection molding machine for flame retardant and double 85 performance tests, and the injection temperature was set at 180~195℃.

[0038] Example 4

[0039] Weigh 1050g of piperazine pyrophosphate, 700g of melamine polyphosphate, 50g of aluminum hypophosphite, 100g of wollastonite, 100g of glass powder, and 75g of nano-hydroxy zinc stannate, and dry them at 70°C for 12h. Then weigh 3750g of homopolymer polypropylene with a melt index of 23g / 10min at 230°C and 2.16kg, 200g of PP-g-MAH compatibilizer, 5g of antioxidant 1010, 10g of antioxidant 168, and 10g of polytetrafluoroethylene powder. Mix the above materials and put them into a high-speed mixer for high-speed stirring for 7min. Then feed the mixture from the main feeding port into a 20-type twin-screw extruder for melt extrusion (twin-screw extruder parameters are: temperature 175°C, speed 300rpm, feeding speed 15Hz, vacuum degree -0.08MPa), and obtain halogen-free environmentally friendly flame-retardant polypropylene composite particles, and then dry the particles at 80°C for 3h.

[0040] Standard specimens were injected into the injection molding machine for flame retardant and double 85 performance tests, and the injection temperature was set at 180~195℃.

[0041] Example 5

[0042] Weigh 600g of piperazine pyrophosphate, 400g of melamine polyphosphate, 60g of diethyl aluminum hypophosphite, 50g of wollastonite, 50g of kaolin, 100g of glass powder, 150g of nano-grade zinc hydroxystannate, and dry them at 70°C for 12h, then weigh 3500g of homopolypropylene with a melting point of 23g / 10min at 230°C and 2.16kg, 50g of PP-g-MAH compatibilizer, 8.3g of antioxidant 1010, 16.7g of antioxidant 168, and 15g of polytetrafluoroethylene powder. Mix the above materials and put them into a high-speed mixer for high-speed stirring for 7min. The mixture was then fed from the main feeding port into a Type 20 twin-screw extruder for melt extrusion (twin-screw extruder parameters were: temperature 175°C, rotation speed 300rpm, feeding speed 15Hz, vacuum degree -0.08MPa) to obtain halogen-free, environmentally friendly, flame-retardant polypropylene composite material particles, which were then dried at 80°C for 3h.

[0043] Standard specimens were injected into the injection molding machine for flame retardant and double 85 performance tests, and the injection temperature was set at 180~195℃.

[0044] Example 6

[0045] Weigh 900g of piperazine pyrophosphate, 600g of melamine polyphosphate, 150g of diethyl aluminum hypophosphite, 100g of wollastonite, 100g of glass powder, and 115g of nano-grade zinc hydroxystannate, and dry them at 70°C for 12h, then weigh 3000g of homopolypropylene with a melting point of 23g / 10min at 230°C and 2.16kg, 100g of PP-g-MAH compatibilizer, 5g of antioxidant 1010, 10g of antioxidant 168, and 20g of polytetrafluoroethylene powder. Mix the above materials and put them into a high-speed mixer for high-speed stirring for 7min. The mixture was then fed from the main feeding port into a Type 20 twin-screw extruder for melt extrusion (twin-screw extruder parameters were: temperature 175°C, rotation speed 300rpm, feeding speed 15Hz, vacuum degree -0.08MPa) to obtain halogen-free, environmentally friendly, flame-retardant polypropylene composite material particles, which were then dried at 80°C for 3h.

[0046] Standard specimens were injected into the injection molding machine for flame retardant and double 85 performance tests, and the injection temperature was set at 180~195℃.

[0047] Comparative Example 1

[0048] Weigh 1050g of piperazine pyrophosphate, 450g of melamine polyphosphate, 50g of aluminum hypophosphite, 300g of wollastonite with a whiteness of 92, and 25g of nano-grade zinc stannate, dry at 70-90°C for 12h, then weigh 2990g of homopolymer polypropylene with a melt index of 25g / 10min, 100g of PP-g-MAH compatibilizer, 5g of antioxidant 1010, 10g of antioxidant 168, and 20g of polytetrafluoroethylene powder. Mix the above materials and put them into a high-speed mixer for high-speed stirring for 8min. Then feed the mixture from the main feeding port into a 20-type twin-screw extruder for melt extrusion (twin-screw extruder parameters are: temperature 175-190°C, speed 300-400rpm, feeding speed 18Hz, vacuum degree -0.08MPa), and obtain halogen-free environmentally friendly flame-retardant polypropylene composite particles, and then dry the particles at 80°C for 3h. Then, standard specimens were injection molded in an injection molding machine for flame retardant and double 85 performance tests, and the injection temperature was set to 180~195℃.

[0049] Comparative Example 2

[0050] Weigh 900g of piperazine pyrophosphate, 600g of melamine polyphosphate, 50g of diethyl aluminum hypophosphite, 300g of glass powder with a whiteness of 88, and 25g of nano-hydroxy zinc stannate, and dry them at 70-90°C for 12h. Then weigh 2990g of homopolymer polypropylene with a melt index of 25g / 10min, 100g of PP-g-MAH compatibilizer, 5g of antioxidant 1010, 10g of antioxidant 168, and 20g of polytetrafluoroethylene powder. Mix the above materials and put them into a high-speed mixer for high-speed stirring for 8min. Then feed the mixture from the main feeding port into a 20-type twin-screw extruder for melt extrusion (twin-screw extruder parameters are: temperature 175-190°C, speed 300-400rpm, feeding speed 18Hz, vacuum degree -0.08MPa), and obtain halogen-free environmentally friendly flame-retardant polypropylene composite particles, and then dry the particles at 80°C for 3h. Then, standard specimens were injection molded in an injection molding machine for flame retardant and double 85 performance tests, and the injection temperature was set to 180~195℃.

[0051] The raw material brands and manufacturers used in the embodiments and comparative examples are as follows:

[0052] Homopolymer polypropylene, melt index of 25g / 10min (test standard ASTM D-1238, test conditions 230℃ / 2.16Kg), brand SK380G, LG Chem, South Korea. Piperazine pyrophosphate, brand PMPP, Yuntianhua Co., Ltd. Melamine polyphosphate, Zhenjiang Xingxing Flame Retardant Co., Ltd. Aluminum hypophosphite, brand FR005, Sichuan Shifang Taifeng New Flame Retardant Co., Ltd. Diethyl aluminum hypophosphite, brand ADP-12, Qingdao Oupu New Materials Co., Ltd. Wollastonite, whiteness>92, D50 is 10~15μm, brand AT-0023T, Jiangxi Aote Technology Co., Ltd. Kaolin, whiteness greater than 92, model DG32BB, Inner Mongolia Chaopai New Materials Co., Ltd. Zinc stannate (ZS), hydroxy zinc stannate (ZHS). Glass powder, brand FJ373, melting point 450℃, Sino-Australia Science and Technology (Shenzhen) New Materials Co., Ltd. Maleic anhydride grafted polypropylene (PP-g-MAH), brand 50E803, DuPont, USA. Antioxidants, Irganox 1010, Irganox 168, BASF, Germany. Anti-drip agent (polytetrafluoroethylene powder), brand SN3307PF, Guangzhou Energy Innovation Materials Co., Ltd.

[0053] Table 1 lists the raw material ratios of various embodiments and comparative examples.

[0054] Table 1: Specific components and proportions of each embodiment and comparative example Unit: g

[0055]

[0056] The flame retardant performance test of the present invention strictly follows the UL94 vertical burning 5VA grade standard. Specifically, the preparation of strip and plate specimens is carried out according to Section 9 of UL 94-2013Rev.14-2022. The strip specimen has a size of 127 mm×12.6 mm×2.0 mm, and the plate specimen has a size of 149 mm×149 mm×2.0 mm.

[0057] 1) Strip sample test method: Fix the strip sample vertically with a clamp, move the Bunsen burner to the bottom of the sample at an angle of 20±5 degrees to the horizontal, use the tip of the blue flame with a length of 125mm to contact the center point of the bottom of the sample and burn for 5±0.5 seconds, then remove the Bunsen burner for 5±0.5 seconds, and repeat this action five times. After removing the flame for the fifth time, observe and record the afterflame time and afterburning time of the sample, as well as whether the cotton is dripped and ignited, and comprehensively judge whether the strip sample is qualified.

[0058] 2) Plate sample test method: Clamp the plate sample horizontally with a fixture, move the Bunsen burner at an angle of 20±5° to the bottom of the plate sample, and let the inner flame contact the center point of the bottom of the plate sample and burn for 5±0.5 seconds. Then remove the Bunsen burner and continue to burn for 5±0.5 seconds. Repeat this action five times. After removing the flame for the fifth time, wait until all residual flames and afterburning completely stop, and observe and record whether the sample is burned through.

[0059] 3) Light and heat aging resistance test (double 85 test): Refer to GB / T 2423.3-2016 standard, and test in a high and low temperature alternating humidity test chamber under the test conditions of 85℃, 85%RH, and 96 hours. Before and after the test, the color difference of the sample is tested with an integrating sphere photometer, using D65 standard light source, 10° observer angle, and the results include specular reflection and 25mm aperture. The color difference value ΔE*ab is measured by an integrating sphere spectrophotometer.

[0060] Table 2 lists the UL94-5VA (2.0 mm), UL94-5VA (3.0 mm), and limiting oxygen index test results of the polypropylene materials prepared in various embodiments and comparative examples.

[0061] Table 2 Test results of UL94-5VA, UL94-5VA and limiting oxygen index of polypropylene materials

[0062]

[0063] Table 3 shows the light and heat aging resistance test results (double 85) of the polypropylene materials prepared in various embodiments and comparative examples.

[0064] Table 3 Results of light and heat aging resistance test of polypropylene materials (double 85)

[0065]

[0066] Based on the above experimental results, it can be seen that all embodiments have successfully achieved the 5VA level flame retardant requirements of 3.0mm and 2.0mm thickness. It is particularly noteworthy that the results of Comparative Examples 1 and 2 emphasize a key point: the use of glass powder and wollastonite or kaolin compound can produce a good synergistic effect, and the material exhibits a good ceramic effect during the combustion process. This effect enables the carbon layer to form a dense ceramic skeleton structure, thereby ensuring that the plate-shaped sample is not penetrated during combustion, and ultimately enables the sample's flame retardant level to reach the 2.0mm 5VA level.

[0067] In addition, in order to achieve a lower color difference ΔE*ab value, wollastonite or kaolin with a whiteness of more than 92 and glass powder with a whiteness of not less than 88 must be selected for compounding. Such a combination can not only ensure the color stability of the product, but also ensure that the masterbatch product can still resist yellowing after aging and successfully pass the double 85 test.

Claims

1. A yellowing-resistant, halogen-free, environmentally friendly, flame-retardant PP composite material, characterized in that: The composite material is composed of the following components in mass fraction: 55-70% polypropylene masterbatch, 20-35% pyropyroxene-based intumescent flame retardant, 1-3% hypophosphite flame retardant, 2-5% inorganic filler, 0.5-3% tin-based flame retardant and smoke suppressant, 2-5% glass powder, 1-4% compatibilizer, 0.3-0.5% antioxidant and 0.2-0.4% anti-dripping agent.

2. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The polypropylene masterbatch is homopolymer polypropylene, and the melting index is ≥20g / 10min at 230°C and 2.16kg.

3. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The pyrophosphate-based intumescent flame retardant is prepared by compounding piperazine pyrophosphate and melamine polyphosphate in a mass ratio of 3:2 to 7:

3.

4. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The hypophosphite flame retardant is one of aluminum hypophosphite and diethyl aluminum hypophosphite.

5. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The inorganic filler is one of wollastonite and kaolin with a whiteness of more than 90.

6. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The tin-based flame retardant and smoke suppressant is one of nano-grade zinc stannate and hydroxy zinc stannate.

7. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The glass powder is FJ373 type glass powder with a melting point of 450° C. and a whiteness of 88 or above.

8. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polypropylene, and the maleic anhydride grafting rate thereof is ≥1%.

9. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The antioxidant is prepared by compounding tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester and tris[2,4-di-tert-butylphenyl] phosphite in a mass ratio of 1:

2.

10. The yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to claim 1, characterized in that: The anti-dripping agent is polytetrafluoroethylene powder.

11. The method for preparing the yellowing-resistant halogen-free, environmentally friendly, flame-retardant PP composite material according to any one of claims 1 to 10, characterized in that: Firstly, the pyropyrene flame retardant, hypophosphite flame retardant, tin-based flame retardant and smoke suppressant, inorganic filler and glass powder are dried, and then mixed with polypropylene masterbatch, compatibilizer, antioxidant and anti-dripping agent, and then the mixture is melt-extruded to obtain UL94-5VA grade yellowing-resistant halogen-free environmentally friendly flame-retardant PP composite material.

12. The method for preparing the yellowing-resistant halogen-free environmentally friendly flame-retardant PP composite material according to claim 11, characterized in that: The drying of the pyropyrocarbon flame retardant, hypophosphite flame retardant, tin-based flame retardant and smoke suppressant, inorganic filler and glass powder is carried out at 70-90° C. for 12 hours; the melt-extrusion of the mixture is carried out by feeding the mixture into a 20-type twin-screw extruder for melt-extrusion.

Citation Information

Patent Citations

  • Halogen-free flame-proof reinforced polypropylene composite material and preparation thereof

    CN101343392A

  • Halogen-free inflaming retarding reinforcing polypropylene composite material and preparation method thereof

    CN102558669A

  • High heat resistant glass fiber enhanced halogen-free flame retardant polypropylene and preparation method thereof

    CN102585378A

  • Halogen-free flame-retardant reinforced polypropylene composite material and preparation method thereof

    CN102936371A

  • UL94-5VA-level high-GWIT (glow wire ignition temperature) enhanced polypropylene composition and preparation method thereof

    CN106995559A